2(x+2)+4=-(x+4)+x

Simple and best practice solution for 2(x+2)+4=-(x+4)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+2)+4=-(x+4)+x equation:



2(x+2)+4=-(x+4)+x
We move all terms to the left:
2(x+2)+4-(-(x+4)+x)=0
We multiply parentheses
2x-(-(x+4)+x)+4+4=0
We calculate terms in parentheses: -(-(x+4)+x), so:
-(x+4)+x
We add all the numbers together, and all the variables
x-(x+4)
We get rid of parentheses
x-x-4
We add all the numbers together, and all the variables
-4
Back to the equation:
-(-4)
We add all the numbers together, and all the variables
2x+12=0
We move all terms containing x to the left, all other terms to the right
2x=-12
x=-12/2
x=-6

See similar equations:

| 11(v+4)-2v=3(3v+1)-9 | | -4(1y+-4y)+3=-3(2y-1y)+1+14y | | 15k=20 | | X+1/14=6/7+x-7/9 | | 427.75=t^2+55t | | (x-5)(x-5)-121=0 | | (x-5)^2-121=0 | | 3(12-5y)=9(2-y)+6(3-y) | | 188=13(s-55)+45 | | y=5(850)-1000 | | 6(7.5-1y)-y=-4 | | 5y-1=4y-5 | | y=-(850)+2000 | | y=-5(850)+3500 | | 9/4x-6=28.5 | | y=(850)-1000 | | y=5(850)+1000 | | y=0.42×64T | | 4(0)-5x=10 | | 7^3x=8^2x | | x+4/2-6=2x-8/3 | | -3y+5(1y-1)=7-6(7-y) | | 4x-5(0)=10 | | -4(y-4y)+3=-3(2y-y)+1+14y | | .2x=x-212 | | x^2-121x+120=0 | | 7+3x=9x-11 | | 8(2n+2)=8(8n+4)+9 | | 2x+10+4-36+4x-34=180 | | x/2+x/3=x/6+4 | | 6x/11=5x/8-7 | | 5(x-3)=17-3x |

Equations solver categories